2012
DOI: 10.1007/s11011-012-9312-z
|View full text |Cite
|
Sign up to set email alerts
|

CYP2D6 genotyping and use of antidepressants in breast cancer patients: test development for clinical application

Abstract: Approximately 25 % of clinically important drugs and numerous environmental carcinogens are metabolised by CYP2D6. Variation in the CYP2D6 gene and concomitant use of tamoxifen (TAM) with certain antidepressants may increase recurrence risk in breast cancer patients due to reduced enzyme activity. In this study we determined the appropriateness of adding CYP2D6 genotyping to the breast cancer genetic testing options already available in South Africa, which include BRCA mutation screening and transcriptional pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…Due to constantly evolving genetic knowledge, the ideal breast cancer susceptibility test remains elusive as it requires continuous development and refinement as new information on VUS classification and clinical relevance of functional polymorphisms become available in the scientific literature. The identification of actionable functional polymorphisms in important disease pathways covered to a certain extent in the CVD multi-gene assay, which was recently extended to include CYP2D6 pharmacogenetics [ 28 , 31 ], caused a paradigm shift in our understanding of the pieces of the susceptibility puzzle. Implications for genetic counseling remains uncertain and can only be comprehended by incorporating fixed genetic and modifiable environmental risk factors into an existing body of knowledge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to constantly evolving genetic knowledge, the ideal breast cancer susceptibility test remains elusive as it requires continuous development and refinement as new information on VUS classification and clinical relevance of functional polymorphisms become available in the scientific literature. The identification of actionable functional polymorphisms in important disease pathways covered to a certain extent in the CVD multi-gene assay, which was recently extended to include CYP2D6 pharmacogenetics [ 28 , 31 ], caused a paradigm shift in our understanding of the pieces of the susceptibility puzzle. Implications for genetic counseling remains uncertain and can only be comprehended by incorporating fixed genetic and modifiable environmental risk factors into an existing body of knowledge.…”
Section: Discussionmentioning
confidence: 99%
“…Only unrelated breast cancer patients with known ER status who signed informed consent for genetic studies were selected for high-throughput genotyping, comprising 60 (37%) Coloured patients of mixed ancestry and 104 (63%) Caucasians, including the index case. Patients with histopathology confirmed breast cancer were recruited at the Tygerberg Hospital Breast Cancer Clinic or referred from private practicing clinicians, as previously described by van der Merwe et al [ 28 ]. Patients referred by clinicians in private practice participated in a chronic disease screen using the CVD multi-gene assay [ 59 ] as the core genetic component, recently extended to include CYP2D6 pharmacogenetics [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that homozygote genotype results in a non-functional protein formation [29]. This non-functional allele was described in association with neuroleptic malignant syndrome [30], metoprolol pharmacokinetics/ pharmacodynamics modulation [31], metoclopramide side effect [32], tamoxifen efficacy [33,34], colchicine efficacy [35], with environmental sensitivity-related illnesses [36], enhancing susceptibility to head and neck squamous cell carcinoma and chemotherapeutic response [37], increased incidence of systemic sclerosis [38] the risk of Parkinson's disease [39] and Poor Metaboliser phenotype for several drugs [40]. Patients with the *4/*4 diplotype and depression may require a lower dose of citalopram, escitalopram, fluoxetine, fluvoxamine, paroxetine or sertraline as compared to patients with the *1/*1 genotype [40].…”
Section: Identified Snpsmentioning
confidence: 99%
“…The enzymes of the cytochrome P450 are primarily responsible for the metabolism of drugs. Specifically, the CYP2D6 isoenzyme is responsible for the metabolism of 20–35% of the most commonly used therapeutic drugs [21] and the gene coding for it has over 70 different polymorphisms, including some specific to certain ethnicities or population groups [12,13,32,53]. In vivo studies of AD have shown that drugs such as bupropion, fluoxetine, quinidine, paroxetine, terbinafine and thioridazine inhibit CYP2D6, leading to adverse effects and poor therapeutic response [1,47].…”
Section: Introductionmentioning
confidence: 99%